Improving Teacher Performance Through The Utilization Of Digital Technology, Work Motivation, And Learning Innovation - Siti Hasanah; Herfina Herfina; Lisa Chandrasari Desianti (UNIVERSITAS PAKUAN, 2025)
Teacher performance at Public Junior High Schools in Central Bogor District was indicated to be suboptimal, particularly in technology adaptation, innovative teaching methods, and intrinsic motivation. This study aimed to empirically analyze the direct and indirect relationships and influences of Digital Technology Utilization, Learning Innovation, and Work Motivation on improving Teacher Performance. This quantitative study employed the Partial Least Squares Structural Equation Modeling (PLS- SEM) method to test the constructed constellation model. The research population consisted of all Public Junior High School teachers in Central Bogor District, Bogor City. The total number of respondents in this study was 173. The results of the structural model test showed that the constructed model has a good fit. This is confirmed by the Goodness of Fit values, namely SRMR =0.029 and NFI = 0.936. Furthermore, the coefficient of determination (R2) for the Teacher Performance variable was 0.538. An R2 value above 0.500 indicates that the model is adequately explaining how much the independent variables are able to explain the dependent variable in the structural model, which is 53.8%. Teacher performance is directly and significantly influenced by the Digital Technology Utilization (X1) variable with a value of 0.447, and by work motivation (X2) with a value of 0.265. These findings provide theoretical contributions in enriching the foundation of education and technology theory, as well as practical benefits for schools and the government in formulating strategies to enhance teacher competence and professionalism in the digital era.